Analysis of Caffeine, Total Phenolic Content, and Antioxidant Activity in Liberica Coffee Beans Roasted by Semi-Automatic and Conventional Methods - Lestari, Lilla Puji (Indonesian Journal of Chemistry and Environment, 2025)
This study aims to evaluate the effect of roasting methods on the chemical and functional properties of Liberica coffee, focusing on caffeine content, total phenolic content (TPC), and antioxidant activity. Two roasting approaches were compared: semi-automatic roasting with controlled conditions, and traditional pan roasting with manual heat regulation. Caffeine levels were determined using UV-Vis spectrophotometry at 273 nm, while TPC was measured using the Folin–Ciocalteu method. Antioxidant activity was assessed via DPPH radical scavenging assay. The results revealed that semi-automatic roasting preserved more bioactive compounds, with higher caffeine content (1.86%) and TPC (56.84 mg GAE/g), compared to conventional roasting (1.34% and 41.27 mg GAE/g, respectively). Antioxidant activity was also significantly higher in semi-automatically roasted samples, with 72.3% inhibition and lower IC₅₀ value (168.5 ppm). These findings indicate that semi-automatic roasting enhances both chemical quality and functional potential of Liberica coffee. The study supports the application of controlled roasting technologies in post-harvest processing to improve the health-related value and market competitiveness of Liberica coffee products.